The Hidden Disequities of Carbon Trading: Carbon Emissions, Air Toxics, and Environmental Justice - Lejano, Raul P.; Kan, Wing Shan; Chau, Ching Chit (Frontiers in Environmental Science, 2020)
So long as transaction costs are low, the creation of a tradeable permit to emit carbon should allow bargaining for emission rights among buyers and sellers, resulting in an efficient allocation of carbon emission rights. However, the trading of carbon credits may have socially unjust consequences. In this article, we explore some hitherto unrecognized disequities. One of these may be the creation of toxic hotspots as the trade of carbon may bring with it a transfer of air toxics, as well. We illustrate the argument by examining emissions from refineries participating in California's cap-and-trade program. These considerations are a concern for the larger question of carbon mitigation as the global community strives to identify feasible, yet just, approaches to reducing greenhouse gas emissions. Contrary to the idea of alienable rights, the transfer of carbon affects people and place in ways not internalized by these market instruments.